Structural Analysis of Gol A Gong's Pucuk Dicinta Ulam Novel Arrives - Simamora, Santi Tiur Minar; Simanjuntak, Harlen; Saragih, Elza L.L (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Literary vocabulary has often been heard by all levels of society, this is because literature has always existed in the midst of society because literature has been attached to daily activities and as an object of literature. The purpose of this study is to describe the structural elements and values contained in the novel "Pucuk Dicinta Ulam Pun Tiba" by Gol A Gong with qualitative research methods. The method used in this study is descriptive, the term descriptive comes from English means to describe or describe something, such as conditions, situations, events, activities and so on. This research will focus on the analysis of themes, plots, characters, and characterizations, as well as points of view drawn from the author's background and the values contained in the novel. Based on etymology, the word literature comes from Sanskrit, namely shastra which is formed from the word shas which means guide and tra which means to direct, teach, instruct, thus literature. In the Big Dictionary Indonesian, literature is defined as the language used in written works such as scriptures or literary works, not colloquial. However, according to Sumardjo and Saini in 1997, literature is seen as an expression of the human person in the form of expressed experiences, thoughts, feelings, ideas, spirits, beliefs.Keywords: Structuralism; Ulam's beloved shoot arrived;